If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = 6x Solving 16 = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 16 + -6x = 6x + -6x Combine like terms: 6x + -6x = 0 16 + -6x = 0 Add '-16' to each side of the equation. 16 + -16 + -6x = 0 + -16 Combine like terms: 16 + -16 = 0 0 + -6x = 0 + -16 -6x = 0 + -16 Combine like terms: 0 + -16 = -16 -6x = -16 Divide each side by '-6'. x = 2.666666667 Simplifying x = 2.666666667
| x^2-3x-8=4 | | -2x^2-28x-98=-512 | | ln(-3x)=ln(x^2-54) | | (-2ab^9)(-6a^3b^9)=0 | | -2.4-4x=7.6 | | 2(3h+2)-4h=0 | | 6h+16=4 | | 15=8-5+2x | | 4(r-9)=8r-32 | | 6x-3=5+4x | | 3x-7=x+21 | | 2(x-3)=1.5(x-4)+x | | 5(z-4)=4z-20 | | 8p=7p | | 0=120-4.9t^2 | | 4n+17+n-2=180 | | 5(9+6)=8p | | (x-16)/3=3x | | Y=6x-17 | | x^2+3x-2.5=0 | | -4x-5y=17 | | 180n-360=s | | x^3-x^2+8x+6=0 | | 3z^3-24z^2+36z=0 | | 6x+17-x=135 | | 12k+6.5=k+15 | | 2*t^2-12t+97=0 | | 12(2-4x)=20(1-2x)-15x+3 | | 12(2-4x)=20(1-2x)-15x+13 | | 9-8k=0 | | 6x-5+7x+3=180 | | (b-g)(b-g)=0 |